Exploiting Intramolecularity: Exploring Aldehyde-Catalyzed Intermolecular Hydroaminations and Mixed Aminal Chemistry - Bilodeau, Didier Alexandre (Université d'Ottawa / University of Ottawa, 2018)
Hydroamination reactions are very attractive to form new C-N bonds, though broadly applicable synthetic methods do not exist. The hydroamination of unactivated alkenes is especially difficult to accomplish given its negative reaction entropy, as well as potentially being a thermodynamically unfavourable transformation with some substrates. Thus, previously reported systems have often consisted of biased intramolecular systems or metal-catalyzed intermolecular variations operating at low temperatures. Recently, our group discovered that intermolecular Cope-type hydroamination of unactivated alkenes is achievable through the use of aldehydes as catalysts. These organocatalysts act solely through promoting the pre-association of reacting partners, hydroxylamines and allyl amines, in order to induce temporary intramolecularity; thus allowing for very mild reaction conditions and access to important 1,2-Diamine motifs. This thesis presents studies expanding upon initial reports of aldehyde-catalyzed Cope-type intermolecular hydroamination. In the scope of these studies standard conditions were developed to compare aldehyde catalytic activity. These evaluations led to further strengthening our understanding of hypothesized trends in aldehydes’ catalytic efficiencies, notably the impact of electronic, steric and solvent effects. Furthermore, the possibility of using a catalytic precursor species for hydroamination was evaluated. While this symmetrical hydroxylamine dimer precursor did not result in increased hydroamination yields, it did allow for easier manipulations as well as allow preliminary kinetic isotope effect studies to study formaldehyde as a precatalyst. These KIE studies allowed to reconfirm that hydroamination was highly likely the rate determining step of our proposed catalytic cycle. Derivatization of hydroamination products was also accomplished to access important 1,2 Diamine motifs from simple starting materials, also allowing to access difficult hydroamination products through the application of quantitative amounts of aldehyde, followed by hydrolysis of the formed heterocycles. Additional studies into nitrone reactivity led us to access a novel synthesis of enantiomerically enriched chiral cyclic nitrones through a sequence of nucleophilic addition, Cope-type hydroamination and Cope elimination. However, this sequence proved unpractical and of very narrow applicability, while affording only modest enantioselectivities (up to 78% ee), therefore further exploration was not warranted. A collaborative study was also undertaken in collaboration with the Wennemers group from ETH Zurich. This exploratory study had the goal of examining the potential for combining small peptide catalysis with aldehyde catalysis inducing temporary intramolecularity. It was hypothesized that the combination of both catalytic systems could improve upon the conjugate addition of nucleophiles to certain electrophiles, such as nitroolefins; in a potentially stereoselective manner. Although initial trials did not yield productive reactions, evidence for potential new mixed aminals with formaldehyde and various nucleophiles was found. Furthermore, the background reactivity of various nucleophile and electrophile pairings was assessed, allowing for better calibration of future efforts in studying such systems.
Keywords: Cope-Type Hydroamination; Organocatalysis; Aldehyde Catalysis; Aminal Chemistry